GE_GERICHTE P/13830/2014 vom 30. Juli 2015 - GE Cour de justice (2015)
ENTRÉE ILLÉGALE; SÉJOUR ILLÉGAL; SURSIS À L'EXÉCUTION DE LA PEINE; PEINE PRIVATIVE DE LIBERTÉ | LEtr.5.1; LEtr.115.1; CP.36.1; CP.41.1; CP.42; CP.47; CP.49.1; CP.52